Family Business Succession: Analysis of Success Drivers Based on Entrepreneurship Theory using NVivo modeling - Satrio Pradelina, Dewa; Margaretha, Yolla (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2024)
This study explores the influence of personal and organizational characteristics on the motivation of successors in family business succession in Indonesia. Through a survey involving 30 respondents from West Java, data were analyzed using NVivo software. Findings indicate that age, gender, and business scale influence successor motivation, especially when succession plans are in place. The research highlights the importance of mature succession planning as a key to family business success. These findings can support the development of more effective policies and improvements in succession process management. Limitations of the study include questions that do not consider the business sector comprehensively and the need for a more varied sample. Future research can enrich this model and address these limitations to deepen understanding of family business succession.